Study of the structural anomaly of liquid water using upconverting thermometry of Brownian nanocrystals - Maturi, Fernando Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Although water is the most commonly used liquid, it is one of the most intriguing substances on planet Earth. This is because, despite having a simple chemical composition and molecular structure, liquid water exhibits an extraordinarily complex behavior when subjected to variations in temperature and pressure, setting it apart from other commonly used liquids. These anomalies in the behavior of water are easily observed under supercooling conditions, where water is cooled to temperatures below its freezing point, remaining in the liquid phase, thus revealing the existence of two distinct liquid states. While considered a remarkable explanation for the occurrence of its anomalous properties, the coexistence of these two liquid states of water is difficult to prove under normal conditions of temperature and pressure. This requires the development of new experimental approaches to investigate the peculiar characteristics of water that make life as we know it possible on our planet. Since the transition between the structures of the two liquid states of water occurs at a local level, the use of techniques capable of observing fluctuations in microscopic events is required. Therefore, this doctoral research work employs the technique of luminescence thermometry as a powerful tool to identify fluctuations between two types of hydrogen bond organizations in water molecules arranged around the surface of Brownian nanoparticles. The obtained results reveal that, in addition to identifying low and high-density liquid domains, the delicate balance between the coexistence of these different water domains is strongly influenced by the size of the nanoparticles and the pH of the aqueous medium, respectively corresponding to variations in temperature and pressure in a newly proposed hypothetical phase diagram of water.

Embora seja o líquido mais utilizado, a água é uma das substâncias mais intrigantes do planeta Terra. Isso ocorre porque, apesar de apresentar composição química e estrutura molecular simples, a água líquida revela um comportamento extraordinariamente complexo quando sujeita a variações de temperatura e pressão, o que a distingue de outros líquidos comumente utilizados. Essas anomalias no comportamento da água são facilmente observadas em condições de super resfriamento, quando a água é resfriada a temperaturas abaixo do seu ponto de congelamento, mantendo-se na fase líquida, e, revelando assim a existência de dois estados líquidos distintos. Apesar de considerada uma explicação notável para a ocorrência de suas propriedades anômalas, a coexistência desses dois estados líquidos da água é difícil de comprovar em condições normais de temperatura e pressão. Isso exige o desenvolvimento de novas abordagens experimentais para investigar as características peculiares da água que tornam a vida como conhecermos possível em nosso planeta. Dado que a transição entre as estruturas dos dois estados líquidos da água ocorre em nível local, é necessária então a utilização de técnicas capazes de observar as flutuações de eventos microscópicos. Portanto, este trabalho de doutorado emprega a técnica de termometria de luminescência como uma ferramenta poderosa para identificar flutuações entre dois tipos de organização de ligações de hidrogênio em moléculas de água dispostas ao redor da superfície de nanopartículas Brownianas. Os resultados obtidos revelam que, além de ser possível identificar domínios líquidos de baixa e alta densidade, o equilíbrio delicado entre a coexistência desses diferentes domínios de água é fortemente influenciado pelo tamanho das nanopartículas e pelo pH do meio aquoso, correspondendo, respetivamente, às variações de temperatura e pressão em um novo diagrama hipotético de fases da água proposto recentemente.
Estudo da anomalia estrutural da água líquida usando termometria por conversão ascendente de energia de nanopartículas Brownianas
Keywords: Água; Anomalias; Luminescência; Movimentos brownianos; Termômetro e termometria; Water; Anomalies; Luminescence; Brownian movements; Thermometer and thermometry